Efficiency of Education Budget Allocation for High School Level in Indonesia - Putri Suryani (Didaktika: Jurnal Kependidikan, 2025)
The efficiency of the education budget is important to measure how optimally the use of limited resources has been used to improve the quality of education. Over the last decade, there has been an increase in education budgets, but this is not in line with increases in educational attainment. Regarding to see the extent of the success of budget management carried out by local governments, it is necessary to measure efficiency by looking at the increase in output from the education budget input. This study uses the Data Envelopment Analysis to measure the success of this efficiency. The results of the efficiency values are then used in Tobit Regression to identify factors that influence the efficiency of education budget at the provincial level. The data used is data from 33 provinces during 2016-2019. DEA results show that there are 9 provinces that have a perfect average efficiency score from 2016-2019. Meanwhile, there are 16 provinces with efficiency values below the average from 2016-2019. From the Oslack analysis, this research also shows the identification of inefficiencies in each output. For example, Central Sulawesi has the potential to increase 6,03 points National Examination Scores and Papua has the potential to increase 12,4% Pure Participation. Meanwhile, through Tobit analysis, this study also shows that the factors that influence the efficiency of the education budget are GRDP, Density, Underdeveloped Province, and Program Indonesia Pintar.